Characterization of effective microorganism (Phosphate solubilizing bacteria) isolated from oil palm field soils / Muhammad Arif Abdullah and Muhammad Nuruddin Mohd Nor - Abdullah, Muhammad Arif; Mohd Nor, Muhammad Nuruddin (Faculty of Plantation and Agrotechnology, 2018)
Phosphate Solubilizing Bacteria (PSB) is one of methods that are not only efficient, but also have a low cost of agricultural input, supplementary, renewable, safe and environmentally friendly are now being the priority in the agricultural industry. This research is focusing on identifying either with the inoculations of phosphate solubilizing bacteria (PSB) gives effect to solubilization of phosphorus in the soil and become available for plant uptake or there is no significance at all. The bacteria were isolated from FELCRA Seri Mendapat oil palm field. To address this, four treatments are set up which are T1 (soil added with PSB-1), T2 (soil added with PSB-2), T3 (soil added with PSB-3) and T4 (soil without PSB) by using Completely Randomized Design (CRD). Available P for the treatments and the value of soil pH are being taken before and after for examining the research samples. Other than that, the growth performance of oil palm seedlings was also recorded with the measurement of oil palm seedling height, number of leaves and the width of oil palm seedling leaves at once a week within two months. The soil analysis for available P and the soil pH was found to have significant increase when treated with PSB as shown in the result. The plant analysis for the growth performance of oil palm seedlings also shows that better growth of plant for the soils that have been treated with PSB. Thus, the application of PSB to the soil can increase the availability of P and reduce the soil acidity. In addition, it gives effect to the performance of the oil palm seedling growth where this research showed an increase of plant height, larger width of the leaves and increase number of leaves compared to the soils that does not treat with PSB. However, to ensure this application can produce significant effects, several effective considerations must be taken.